Comparison of Ab Initio Quantum Chemistry With Experiment for Small Molecules 1985
DOI: 10.1007/978-94-009-5474-8_13
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Dissociation Energies for Ionic Molecules

Abstract: Ab initio calculations at the self-consistent-field and singles plus doubles configuration-interaction level are used to determine accurate spectroscopic parameters (D e , r e , u e ) for most of the alkali and alkaline-earth fluorides, chlorides, oxides, sulfides, hydroxides and isocyanides. Numerical Hartree-Fock (NHF) calculations are performed on selected systems to ensure that the extended Slater basis sets employed for the diatomic systems are near the Hartree-Fock limit. Extended gaussian basis sets of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 106 publications
2
2
0
Order By: Relevance
“…Looking into another source of thermochemical data, CRC Handbook of Chemistry and Physics , we find the value of 86.8 ± 3.0 kcal/mol for the bond strength in MgO. Earlier ab initio calculations by Bauschlicher and co-workers resulted in 63.4 kcal/mol which is much closer to the QCISD(T)/6-311+G(3df) value than to the experimental results. The existing uncertainty concerning the bond strength and standard heat of formation for MgO prompted us to reinvestigate energetics of this molecule using highly accurate multireference configuration (MRCI) method …”
Section: Resultssupporting
confidence: 57%
“…Looking into another source of thermochemical data, CRC Handbook of Chemistry and Physics , we find the value of 86.8 ± 3.0 kcal/mol for the bond strength in MgO. Earlier ab initio calculations by Bauschlicher and co-workers resulted in 63.4 kcal/mol which is much closer to the QCISD(T)/6-311+G(3df) value than to the experimental results. The existing uncertainty concerning the bond strength and standard heat of formation for MgO prompted us to reinvestigate energetics of this molecule using highly accurate multireference configuration (MRCI) method …”
Section: Resultssupporting
confidence: 57%
“…The agreement between the Herzberg and Brewer and Brackett values (columns (g) and (h)) is striking and we have used the average of these values in our analyses. The measurements of Brewer and Brackett 43 are also in good agreement with theory 48 . We stress that our conclusions do not change when the other (slightly different) values are used.…”
Section: Resultssupporting
confidence: 88%
“…The measurements of Brewer and Brackett 43 are also in good agreement with theory. 48 We stress that our conclusions do not change when the other (slightly different) values are used.…”
Section: Reference Data For Gas-phase Alkali Halidesmentioning
confidence: 56%
“…With the minimal VB structure set, the VB wave function correlates with restricted open-shell Hartree−Fock (ROHF) states of the TM + and H. Because the HF level treats poorly the atomic states and especially the 3d n +1 state, the deficiencies in the atomic calculation will carry over to the BDE values, even if the molecular calculation is correct. Goddard et al and Bauschlicher et al , showed that the deficiencies can be avoided by correcting the energies of the TM + fragment using experimental atomic data. Thus, the TMH + species are dissociated into the atomic electronic states most closely resembling their situation in the molecule (i.e., for TM + it is the 4s 1 3d n state), and whenever necessary, the experimental atomic state splitting is used to correct the energy of the TM + fragment to the corresponding atomic ground state.…”
Section: Methodsmentioning
confidence: 99%